Furlow Palatoplasty: Should We Also Focus on the Size of the Nasopharynx?. (November 2021) - Leclerc, Jacques E.; Gilbert, Francis; McConnell, Élisa-Maude; Beaudoin, Ericka; Bouchard, Johanie; Simonyan, David
Objectives: (1) To determine the incidence rate of velopharyngeal dysfunction (VPD) according to 7 speech criteria post-Furlow palatoplasty. (2) To find an anatomical measurement of the cleft palate (or combination of measurements) associated with the occurrence of VPD. Study design: Retrospective cohort study. Participants and Methods: Fifty-six patients with cleft palate ± cleft lip underwent palatoplasty with the Furlow technique at the age of 10 months. Pre-and post-palatoplasty cleft palate measurements were collected during the procedure. Three blinded speech-language pathologists (SLPs) retrospectively scored the patients from the chart data at age 4. Student t test and receiver operating characteristic curve analysis were used to evaluate the association and predictive capacity between cleft measurements and parameters (M&P) with all VPD criteria. Results: The SLPs found an incidence of VPD according to 7 criteria: hypernasality (11%), audible nasal emission (4%), nasal rustle (14%), compensatory errors (4%), impairment of speech understandability (7%), and impairment of speech acceptability (16%). The SLPs recommended a secondary surgical procedure in 5 patients (9%). A statistically significant association was found between, respectively, 17 and 5 M&P and the occurrence of compensatory errors and audible nasal emission. Our data suggest that the length of the cleft, the cleft area, and the postoperative transversal size of the nasopharynx are the best indicators of the future positivity of VPD criteria. Conclusion: The size of the postoperative transverse nasopharyngeal area during the primary cleft palate procedure may become the focus of the next generation of cleft surgeons to reduce the incidence of VPD.